Business models towards achieving sustainability: a general review - Marcelino-Aranda, Mariana; Martínez-Cuevas, María del Carmen; Camacho, Alejandro D.; Ortega-Reyes, Antonio Oswaldo; Torres-Ramírez, Aylin (Unidad Editorial UPTC, 2024)
Sustainability is a term that has prevailed for decades, from the concern to generate a balance between economic growth and nature, to its integration into the business environment. The latter began for ethical reasons, then as a requirement to comply with regulatory aspects and, recently, according to evidence, to increase market value. The objective of this paper is to present a general review of the different proposals of business models with a sustainable approach, to understand their characteristics, limitations, and the value they offer. A qualitative perspective was applied, through a systematic review of the literature in the Web of Science (WoS) research portal of Clarivate Analytics, and an analysis of 40 documents. Due to their relevance, five proposals stand out: Sustainable Business Model, Green Business Model, Circular Business Model, Sustainable Business Model Innovation, and Green Business Model Innovation. Positioning a company as sustainable implies not only aligning economic objectives with the needs of society and the environment, but also generating and promoting the necessary changes to achieve it. JEL Codes: M10, Q51, Q56. Received: 23/11/2023.  Accepted: 14/03/2024 Published: 19/04/2024.